Physicochemical and structural characterization of surface modified electrospun PMMA nanofibre - Rabiatul Adawiyah Razali; Yogeswaran Lokanathan; Shiplu Roy Chowdhury; Aminuddin Saim; Ruszymah Haji Idrus (Penerbit Universiti Kebangsaan Malaysia, 2018)
Although electrospun poly(methyl methacrylate) (PMMA) may mimic structural features of extracellular matrix, its highly hydrophobic nature causes reduced cell attachment. This study analysed the physicochemical and structural changes of the surface modified PMMA nanofiber. The electrospun PMMA nanofibers (PM) were surface-treated as follows: PM alone, collagen coated-PM (PM-C), UV-irradiated PM (PM-UV), collagen coated UV-irradiated PM (PM-C-UV) and collagen coated-PM crosslinked with genipin (PM-C-GEN). They were subjected to scanning electron microscopy, Fourier transform infrared (FTIR), cell attachment analysis, X-ray photoelectron spectroscopy (XPS), atomic force microscopy and X-ray powder diffraction (XRD). The surface roughness was lower in PM-C-UV group compared to others. Based on FTIR results, all expected functional group were present in all groups. XPS result showed that there are changes in the mass concentration of UV-treated surfaces and in the collagen coated surfaces. All PM groups showed amorphous nature through XRD. UV irradiation and collagen coating were shown to increase PM’s functional groups and modify its surface, which contributed to the increased attachment of cells onto the inert PM scaffold. As conclusion, collagen coated UV irradiated PMMA provided a better surface for cell to attach hence are suitable to be used further as scaffold for in vitro model.